Seroprevalence of hepatitis A virus, hepatitis B virus, hepatitis C virus, and syphilis among human immunodeficiency virus-infected people at a university hospital, Turkey - Heval Can Bilek; Aydın Deveci; Esra Aksakal Tanyel (Archives of Medical Science)
Introduction Infections such as viral hepatitis and syphilis that share similar transmission routes with human immunodeficiency virus (HIV) may adversely affect the course of the disease. We aimed to determine the seroprevalence of viral hepatitis and syphilis among HIV-infected people at the initial stage of diagnosis.